Reproduction of trichospilus diatraeae (Hymenoptera: Eulophidae) in the pupae of diaphania hyalinata (Lepidoptera: Crambidae) of various ages - Da Silva, Isabel Moreira; Zanuncio, Teresinha Vinha; Pereira, Fabricio Fagundes; Wilcken, Carlos Frederico [UNESP]; Serrão, José Eduardo; Zanuncio, José Cola (De Gruyter, 2015)
Trichospilus diatraeae Cherian & Margabandhu (Hymenoptera: Eulophidae) is a gregarious parasitoid of a wide variety of lepidopterans including melonworm, Diaphania hyalinata L. (Lepidoptera: Crambidae), pupae in the field. The latter is a key pest of Cucurbitaceae; it primarily damages their leaves and secondarily their fruit, and it reduces the productivity of the plants. The aim of this study was to determine the effect of the age of D. hyalinata pupae on the development of T. diatraeae. Diaphania hyalinata pupae aged 24, 48, 72, 96, 120, and 144 h were individualized and exposed to eight 48-h-old T. diatraeae females for 24 h. The emergence and parasitism rates, sex ratios, and longevities of T. diatraeae males and females were found to be similar with D. hyalinata pupae of different ages. The number of progeny, width of the head capsule, and duration of the life cycle (egg to adult) of T. diatraeae decreased with the increasing age of D. hyalinata pupae. Importantly, the number of parasitoid progeny per host pupa and size of the parasitoid adults were larger when 24-h-old host pupae were parasitized than when 48- to 144-h-old pupae were parasitized. Trichospilus diatraeae was very effective in parasitizing D. hyalinata pupae of ages ranging from 24 to 144 h.
Keywords: host pupa age; host quality; oviposition